Relative Resistance of Certain Clones of Tectona grandis to Teak Leaf Skeletonizer, Eutectona machaeralis Walk. (Lepidoptera : Pyralidae) - Meshram, P. B.; Joshi, K. C.; Sarkar, A. K. (Indian Forester, 1994)
Eleven selected clones of teak, Tectona grandis belong to Andhra Pradesh, Mabarashtra, Orissa, Tamil Nadu and Uttar Pradesh were evaluated for their natural variation in suspectibility to teak leaf skeletonizer, Eutectona machaeralis Walk. APT-20, APT-8 and MHSCJ-2 were observed to be the most resistant clones as the leaf areas consumed by the larvae were 1.07, 2.13 and 3.94 cm2. Whereas UPD-1 followed by TNT-11 were the most suspectible (leaf area fed being 9.46 and 6.87 cm2).